Pediatric mechanical circulatory support: pathophysiology of pediatric hemostasis and postoperative management algorithms - N. N. Koloskova; T. A. Khalilulin; D. V. Ryabtsev; V. N. Poptsov (Вестник трансплантологии и искусственных органов)
Chronic heart failure (CHF) against the background of congenital heart disease, mostly in early childhood, or various forms of cardiomyopathies, more common in teenage age, represents an important cause of morbidity and mortality in the pediatric population [1, 2]. Due to the increase in the number of patients suffering from refractory end-stage CHF over the last two decades, and the current shortage of donor organs in pediatric practice, the issue of long-term mechanical circulatory support (MCS) is becoming increasingly a pressing problem. Patient management is a multidisciplinary task, since prolonged use of anticoagulant and antiplatelet therapy to prevent ventricular thrombosis has potentially life-threatening complications - acute hemorrhagic stroke and bleeding of varying severity.